2022
DOI: 10.3390/inorganics10050067
|View full text |Cite
|
Sign up to set email alerts
|

TiO2-La2O3 as Photocatalysts in the Degradation of Naproxen

Abstract: The indiscriminate use of naproxen as an anti-inflammatory has been the leading cause of pollution in sewage effluents. Conversely, titanium dioxide is one of the most promising photocatalyst for the degradation of pollutants. Ti-La mixed oxides containing 0, 1, 3, 5, and 10 wt.% of lanthanum were synthetized by sol-gel and tested as photocatalysts in the degradation of naproxen (NPX). The materials were further characterized by X-ray diffraction (XRD), nitrogen physisorption (BET), scanning electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…The TEM analysis carried out in an earlier study showed that doping of La 3+ resulted in a narrower particle size distribution compared to pure TiO 2 nanoparticles [15]. The La doping led to a lower particle size distribution, consistent with XRD results (Table -2) [16].…”
Section: X-ray Diffraction (Xrd)supporting
confidence: 81%
See 1 more Smart Citation
“…The TEM analysis carried out in an earlier study showed that doping of La 3+ resulted in a narrower particle size distribution compared to pure TiO 2 nanoparticles [15]. The La doping led to a lower particle size distribution, consistent with XRD results (Table -2) [16].…”
Section: X-ray Diffraction (Xrd)supporting
confidence: 81%
“…Fig. 9c shows the XPS peaks corresponding to La 3d3/2 and 3d5/2 appeared at binding energies of 839 and 852 eV, respectively attributing the presence of Ti-O-La bonds [16]. whereas Fig.…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 98%
“…This study addresses the environmental issue of naproxen pollution in sewage effluents, which is primarily caused by its widespread use as an anti-inflammatory drug. To combat this problem, the researchers investigated the use of titanium dioxide (TiO 2 ) as a promising photocatalyst for degrading naproxen (NPX) [21].…”
Section: Tio 2 -La 2 O 3 As Photocatalyst In the Degradation Of Naproxenmentioning
confidence: 99%
“…The researchers synthesized Ti-La mixed oxides with varying lanthanum (La) contents (0, 1, 3, 5, and 10 wt.%) via the sol-gel method. These mixed oxides were tested as photocatalysts for the degradation of naproxen [21].…”
Section: Tio 2 -La 2 O 3 As Photocatalyst In the Degradation Of Naproxenmentioning
confidence: 99%
See 1 more Smart Citation